Pengembangan Media Kartu Kuartet Menggunakan Aplikasi Canva Mapel IPAS Bab 6 “Indonesiaku Kaya Budaya” Kelas IV SDN 2 Duwet - Zahrotun Nisak; Nugrananda Janattaka (Journal on Education, 2024)
Research on the development of IPAS Quartet Cards Chapter 6 Indonesia Rich in Culture based on the lack of learning media in a classroom, the lack of learning media used in the learning process. Learning activities only use monotonous learning media such as agile smart books, student books that can only support the learning process. In accordance with the Merdeka Curriculum used, directing students to learn creatively and actively requires varied, interesting learning media so that students can contribute well, the aim is to describe the quartet card development process. This learning media is designed to provide a new sensation in lessons. This research is a Research and Development study that uses the Borg and Gall model. The validity of the quartet card media was measured by media, material and language experts through validation instruments. While the quartet card response questionnaire was obtained through a questionnaire given to 15 students and 1 educator. The results showed that the level of validity of the Quartet Card was in accordance with the results of the expert validation questionnaire score. The results of the validity of the media expert 90% “Very Valid”. The results of the material expert assessment 92.5% “Very Valid”. The results of the assessment of language experts 93.75 category “Very Valid” concluded that the Quartet Card learning media fell into the “Valid” category.